HUBUNGAN ANTARA DUKUNGAN SOSIAL TEMAN SEBAYA DENGAN AKTUALISASI DIRI MAHASISWA JURUSAN KEPERAWATAN FAKULTAS KEDOKTERAN UNIVERSITAS DIPONEGORO - Atun Sa’diyati Widyaningsih; Diyan Yuli Wijayanti (IJNP (Indonesian Journal of Nursing Practices), 2015)
Background: Self-actualization is psychology needs to grow, develop, and use the skills and also manage oneself so that can be independent neither internal nor external pressure. According to Maslow, less than 1% people can reach of self-actualization. The reached of self-actualization by individual not released without the social supports from individual closest persons, like peer social support.Objective: The purpose of this research was to know the relationship between peer social support with self-actualization college students School of Nursing Faculty of Medicine Diponegoro University. Methods: The type of this research was non-experimental quantitative with descriptive correlation. The samples of this research amount 153 that taken by Proportionate Stratifi ed Random Sampling technique. Result: The result of statistical test with Spearman Rank was ρ value = 0.015 (ρ 0.05). It means that there was a relationship between peer social support with self-actualization in college students School of Nursing Faculty of Medicine Diponegoro University.Conclusion: College students should be more active in lectures activities, both academic and non academic to increase their self-actualization.Keywords: self-actualization, peer social support, college student